Search for promptly produced heavy quarkonium states in hadronic Z decays - Abreu, P; Adam, W; Adye, T; Agasi, E; Ajinenko, I; Aleksan, R; Alekseev, G; Allport, P; Almehed, S; Alvsvaag, S; Amaldi, U; Amato, S; et al. (1995)
A search has been made for direct production of heavy quarkonium states in more than 3 million hadronic Z 0 decays in the 1991-1994 DELPHI data. Prompt J/ψ, ψ(2 S) and Γ candidates have been searched for through their leptonic decay modes using criteria based on the kinematics and decay vertex positions. New upper limits are set at the 90% confidence level for Br(Z 0→(Qq)X)/Br(Z 0→ hadrons) for various strong production mechanisms of J/ψ and Γ; these range down to 0.9×10-4. The limits are set in the presence of a small excess (∼1% statistical probability of a background fluctuation) in the sum of candidates from prompt J/ψ, ψ(2 S), γ(1 S), γ(2 S) and γ(3 S) relative to the estimated background. © 1996 Springer-Verlag.